New material for wearing in abrasive conditions - Дворук, В. И.; Шевеля, И. В.; Радченко, А. В. (Proceedings of National Aviation University (archive), 1999)
Substantiated is the expediency of the principle of using "spring" for the creation of wear resistant materials in conditions of abrasive wearing, on the basis of which new material is created. Proved experimentally is high efficiency of new material, which solves the problem of increasing abrasive-wear resistance of cylinder bushes for bore pumps